Recurrent salivary pleomorphic adenoma shows increased immunohistologic expression of bcl-2 oncoprotein - Obtulovicova, Katarina; Starek, Ivo; Salzman, Richard; Kalis, Adrian; Ehrmann, Jiri; Sicak, Marian; Dvorackova, Jana (Biomedical papers, 2015)
Background: Internal cell biology, including apoptotic regulation, is presumed to play a key role in the development of recurrent pleomorphic adenoma (PA).Aim: The aim of our study was to determine the relevance of B-cell lymphoma 2 (bcl-2) oncoprotein immunoexpression and distribution in primary PA, and its recurrence.Methods: Ten primary-non-recurrent, 14 primary-to-recur, and 28 recurrences of parotid PA patients aged 19-73 (mean 40.7±16.7) years were enrolled. The bcl-2 expression was compared between groups using a semi-quantitative histoscore, defined as the multiple of the percentage of cells by the intensity of immunostaining.Results: Widely varying bcl-2 immunoreaction was found in the epithelial areas of 91.7% of primary and 85.2% of recurrent PA. Similarly varying but much less, immunopositivity was found in the myxoid areas of 62.5% of primary and 71.4% of recurrent tumours. No obvious differences in the bcl-2 staining intensity or pattern of specific epithelial morphologic structures in either the primary-non-recurrent, primary-to-recur or recurrent tumours were found. In both the mesenchymal and epithelial areas of PA, the differences in bcl-2 immunohistoscore between the primary-non-recurrent and primary-to-recur groups were not statistically significant (P=0.62, respectively 0.51). In the mesenchymal areas, the study revealed a significantly increased histoscore in recurrent tumours compared to their corresponding primaries (P=0.01). Increased bcl-2 expression in recurrent PA suggests an exaggerated aggressiveness of that tumor. Conclusion: The fact that a significant difference in the histoscore was found exclusively in the myxoid component seems to accord with the reported prevalence of the latter in recurrent and metastatic PA.
Keywords: apoptosis; bcl-2 gene; recurrence; pleomorphic adenoma; mesenchymal stromal cells